Internationalization of promising local enterprises : the role of human capital. - Heng, Judy Sze Tiang. (2008)
This project seeks to find out how we can nurture our own companies and industries, so as to provide support to MNCs as well as to build up knowledge-intensive capabilities and develop indigenous products and technologies. A model is henceforth generated to assist the many local companies to achieve international economic success.